Reducing explicit and implicit outgroup prejudice via direct and extended contact the mediating role of self-disclosure and intergroup anxiety. [article]. - Turner, Rhiannon N.
In 4 studies, the authors investigated mediators of the effect of cross-group friendship. In study 1, cross-group friendship among White elementary school children predicted more positive explicit out-group attitude toward South Asians, mediated by self-disclosure and intergroup anxiety. In study 2, cross-group friendship and extended contact among White and South Asian high school students positively predicted explicit outgroup attitude, mediated by self-disclosure and intergroup anxiety. Study 3 replicated these findings in a larger independent sample. Study 4 further showed that self-disclosure improved explicit outgroup attitude via empathy, importance of contact, and intergroup trust. The authors discuss the theoretical and practical implications of these findings, which argue for the inclusion of self-disclosure as a key component of social interventions to reduce prejudice. -- (from the author)
Keywords: Cross-group friendship; Extended contact; Self-disclosure.; Intergroup anxiety; Explicit and implicit attitudes